Acercamiento multi-objetivo para la minimización de casos de prueba en Líneas de Producción de Software. - Alarcón-Jaén, Javier Norberto (My University, 2018)
Currently many developments are guided by customers, and therefore, most companies focus on the needs of their potential customers by creating a software product line -a portfolio of products closely related to variations in features and functions- rather than just a single product. The tools and techniques for the common development of software tend to focus individual products and development, of such multiple and interrelated products, is complex. The main objective of this project is develop an optimization strategy to dealt with the previous problem and it allows us to reduce the number of test cases to apply in a reasonable time, but maintaining the quality of the resulting software products. Finally, we compare results using several different algorithms (monoobjective and multi-objectives approaches).
Multiobjective approaches for the minimization of test suites in Software Product Lines.
Keywords: Ingeniería del software; Grado en Ingeniería del Software - Trabajos Fin de Grado; Informática - Trabajos Fin de Grado; Optimization; Multi-objective; GA (genetic algorithm); Random search; Pareto front; Software product lines; Test cases